Evaluation of the Relationship Between Health Literacy and the Perspectives of Pregnancy on Covid-19 Vaccines During the Covid-19 Pandemic Period - AKMAN, BÜŞRA NUR (Scientific Reports in Medicine, 2024)
Objective: The aim of this study was to investigate the number of pregnant women who were exposed to COVID-19 during the COVID-19 pandemic their perspectives on vaccines, their vaccination status, their attitude towards vaccines, and to evaluate the relationship between their approaches and health literacy.The population of the study, Kastamonu Training and Research Hospital and those who have at least four weeks of pregnancy who apply to İnebolu State Hospital, and covering all other trimester periods (N = 375). Attitudes and behaviors towards vaccines Survey Questionnaire in order to determine and determine health literacy levels Turkey Health Literacy Scale-32 was used. Results: The mean age of pregnant women was 28.40±5.61 and the mean gestational week was 28.405.61 22.69±11.47. In the study, 69.1% of pregnant women had COVID-19 disease. caught, 76% received COVID-19 vaccine and 9.3% were during pregnancy. Infecting the family of 68% of pregnant women with the disease pregnancy because they got the COVID-19 vaccine against their will, and 90.7% of them were pregnant Pregnant women’s TSOY-32 The mean overall index score of the scale was 23.37 ± 8.35. 55.7% of pregnant women It was determined that there was insufficient health literacy level. Conclusion: As a result of the study, COVID-19 vaccines during the COVID-19 pandemic Health literacy of pregnant women who are determined to show approaches, attitudes and behaviors It was determined that their levels were insufficient. These results, health The level of knowledge of pregnant women with low health literacy about COVID-19 vaccines It should be increased.